Immunoproteasome in the blood plasma of children with acute appendicitis, and its correlation with proteasome and UCHL1 measured by SPR imaging biosensors. (16th October 2017) - Matuszczak, E.; Sankiewicz, A.; Debek, W.; Gorodkiewicz, E.; Milewski, R.; Hermanowicz, A.
Summary: The aim of this study was to determinate the immunoproteasome concentration in the blood plasma of children with appendicitis, and its correlation with circulating proteasome and ubiquitin carboxyl‐terminal hydrolase L1 (UCHL1). Twenty‐seven children with acute appendicitis, managed at the Paediatric Surgery Department, were included randomly into the study (age 2 years 9 months up to 14 years, mean age 9·5 ± 1 years). There were 10 girls and 17 boys; 18 healthy, age‐matched subjects, admitted for planned surgeries served as controls. Mean concentrations of immunoproteasome, 20S proteasome and UCHL1 in the blood plasma of children with appendicitis before surgery 24 h and 72 h after the appendectomy were higher than in the control group. The immunoproteasome, 20S proteasome and UCHL1 concentrations in the blood plasma of patients with acute appendicitis were highest before surgery. The immunoproteasome, 20S proteasome and UCHL1 concentration measured 24 and 72 h after the operation decreased slowly over time and still did not reach the normal range ( P < 0·05). There was no statistical difference between immunoproteasome, 20S proteasome and UCHL1 concentrations in children operated on laparoscopically and children after classic appendectomy. The immunoproteasome concentration may reflect the metabolic response to acute state inflammation, and the process of gradual ebbing of the inflammation may thus be helpful in the assessment of the efficacy of treatment. The method of operation – classic open appendectomy or laparoscopic appendectomy – does not influence the general trend in immunoproteasome concentration in children with appendicitis. Abstract : Immunoproteasome, 20S proteasome and UCHL1 concentration in the blood plasma of children with appendicitis were highest before the surgery, slowly decreased over time, and 72 hours after the operation, still did not reach the normal range, as measured in controls. The immunoproteasome concentration may reflect the metabolic response to acute state inflammation, and the process of gradual ebbing of the inflammation, thus may be helpful in the assessment of the efficacy of treatment. The method of operation – classic open appendectomy, or laparoscopic appendectomy, does not influence the general trend in immunoproteasome concentration in children with appendicitis.